A seven year experience in patients undergoing total thyroidectomy for benign diseases in a single unit of tertiary care centre: a retrospective case study - Kalwaniya, Dheer S.; Bajwa, Jaspreet S.; Gowda, Gowtham K.; Narayan, Akshay; Choudhary, Rohit (International Journal of Research in Medical Sciences, 2019)
Background: Thyroidectomy is a common surgical procedure performed worldwide by surgeons with varied training. It is the experience and the skills by which a surgeon performs, the indication of surgery and the extent of surgery which determines the outcome and the complication rates. Method: This study is a retrospective study performed from January 2012 to December 2018 when a total of 170 patients underwent total thyroidectomy via kocher’s incision for benign diseases with clinically in hypothyroid state at Safdarjung Hospital, New Delhi in a single unit of a tertiary care hospital. Results: The male: female ratio was 1:7.09 with average age of patients being 40years. The overall complication rate was 18.82% (32 patients). Postoperative transient hypocalcaemia being the most common complication. There was no case of permanent hypocalcaemia. There was no injury to any nerve (recurrent or superior laryngeal). Transient recurrent laryngeal paresis was noted in 4(2.35%) which resolved with conservative management. Complications like wound infection, sympathetic chain injury were not noted. The characteristic feature of this study was five cases of giant secondary retrosternal goitre which had average weight of greater than 500 grams which were operated using kocher’s incision. The average weight of other 165 patients was 70grams +/- 12 grams. There were no major post-operative complications except for post-operative recurrent laryngeal nerve paresis and seroma formation which was evacuated after 3 weeks of surgery. Conclusion: Hence, from this it is concluded that it is the surgical experience and skills of the surgeon which make total thyroidectomy a safe procedure providing permanent cure with a low post-operative morbidity risk even with large sized retrosternal thyroid glands which can be operated via neck incision.